Weight Training, Aerobic Physical Activities, and Long-Term Waist Circumference Change in Men - Mekary, Rania A.; Grontved, Anders; Despres, Jean-Pierre; Moura, Leandro Pereira de [UNESP]; Asgarzadeh, Morteza; Willett, Walter C.; Rimm, Eric B.; Giovannucci, Edward; Hu, Frank B. (Wiley-Blackwell, 2015)
ObjectiveFindings on weight training and waist circumference (WC) change are controversial. This study examined prospectively whether weight training, moderate to vigorous aerobic activity (MVAA), and replacement of one activity for another were associated with favorable changes in WC and body weight (BW).MethodsPhysical activity, WC, and BW were reported in 1996 and 2008 in a cohort of 10,500 healthy U.S. men in the Health Professionals Follow-up Study. Multiple linear regression models (partition/substitution) to assess these associations were used.ResultsAfter adjusting for potential confounders, a significant inverse dose-response relationship between weight training and WC change (P-trend<0.001) was observed. Less age-associated WC increase was seen with a 20-min/day activity increase; this benefit was significantly stronger for weight training (-0.67 cm, 95% CI -0.93, -0.41) than for MVAA (-0.33 cm, 95% CI -0.40, -0.27), other activities (-0.16 cm, 95% CI -0.28, -0.03), or TV watching (0.08 cm, 95% CI 0.05, 0.12). Substituting 20 min/day of weight training for any other discretionary activity had the strongest inverse association with WC change. MVAA had the strongest inverse association with BW change (-0.23 kg, 95% CI -0.29, -0.17).ConclusionsAmong various activities, weight training had the strongest association with less WC increase. Studies on frequency/volume of weight training and WC change are warranted.